Hotel Management in Muang District, Phayao Province to Support the New Normal Tourists - Khawatkun, Krantharat (Hatyai Academic Journal, 2023)
The purposes of this research were to examine tourist behaviors in using services of hotels in Muang District of Phayao Province and to study hotel business management to support the "new normal" in tourism. The instruments for collecting data were 1) a questionnaire and samples were 260 people selected by applying accidental sampling and the data were analyzed through descriptive statistics, and 2) an interview with 30 informants selected by using purposive sampling as well as using content analysis by organizing and coding the data. The findings were that staff attention and service (42.31%) is the main factor influencing tourists' decisions to chose a place to stay, followed by cleanliness and safety (33.85%). The guidelines for hotel business management should include the following four management approaches: 1) the management of assuring safety; 2) the management of marketing; 3) the management of services; and 4) the management of employees. These four approaches would be managed through the concept of the "new normal” by increasing attention to hygiene, cleanliness, safety, and using various technologies in providing services.